Innovations in savings and credit groups: evidence from Kenya - Roy Mersland (Enterprise Development & Microfinance, 2007)
This article reports from a church-based savings and credit group's project called Tuinuane, in Kenya. The project builds upon the Worth programme of PACT, but has added some interesting and innovative features allowing country-wide outreach. First, it utilizes a church institution; second, it avoids the use of field officers and instead group leaders are screened and trained through a detailed implementation plan; and third, it uses mobile phones in planning, monitoring and follow-up efforts. The attachment to the church and access to mobile phones makes plausible, low-cost, long-term contact with mature groups.
Keywords: 650